Islamic subject teacher and his role in Education (Journal Of Educational and Psychological Researches, 2017)
Using the traditional methods in teaching Islamic subject have neglected student's role and focus mainly toward teacher. Thus, the role of student in teaching process would take a negative side: following these methods cannot achieve the educational objectives of Islamic subject. Teachers who give Islamic subject do not have a full knowledge of the appropriate techniques in teaching. They lack the scientific background that qualify them for teaching. The weakness of knowledge that face Islamic teachers have arisen over different stages of education which showed their lacking in the provision of intonation and interpretation of the Quran as well as the utterance of Prophet Mohammed Hadiths. It takes time to train teachers to do a big job like this because it requires a fundamental change in the cognitive and believes construction.